"Espelho Diário" Corpo(s)-Arte de Rosângela Rennó na perspectiva discursiva - Süssenbach, Carla (2017)
The analysis of the video installation “Espelho Diário” made by the artist Rosângela Rennó aims to comprehend the different sense productions of the female body on the artistic act. The research inserts itself on the theorical field of the pecheutian Speech Analysis and its interlocution with, marked by a saying place of history, ideology and also by the social aspects, what permitted the construction of an analytic device concerned to the materiality of the Artistic Discourse. The analytic theorical device runs different discursive notions, notoriously: file/device, text/textuality, function/effect author, sensible projections/body-picture. The analytic act also establishes a theorical listening concerning to contemporaneous art and the questions which imply the body such as on the performance language as well as the social body determined by the performative acts. Sensible projections is a notion taken to comprehend the body-picture of Rosângela Rennó, whereas an act on the Artistic Discourse, act constituted on and by the contradiction. This operation is marked by the paraphrastic movements of bodies already mentioned throughout the artistic movements along history, as well as own polysemic movements, of the artistic and the contemporaneous. This way, the discursive perspective permitted opacity comprehension and the sense displacement present on the contemporaneous production of the videoinstallation “Espelho Diário”.